Endogenous heparin activity is decreased in peripheral arterial occlusive disease. - Shankar, V; Handa, A; Hands, L (2008)
BACKGROUND: Naturally occurring heparin-like activity in the form of endogenous heparin and heparin sulfate proteoglycans has been shown in normal human plasma. Exogenous low-dose heparin improves pain-free walking distance and maximum walking distance in peripheral arterial occlusive disease (PAOD). Is reduced endogenous heparin activity responsible for some of the problems found in PAOD? This study compared heparin-like activity in patients with PAOD with that in healthy subjects and explored its relationship to disease severity. METHODS: In part 1, native and heparinase-modified thromboelastography was performed on peripheral venous blood samples in three groups of patients to measure heparin-like anticoagulant activity. Group 1: 15 control subjects (median age, 60 years; range, 49-74 years; ankle-brachial pressure index [ABPI] >0.9); group 2: 14 patients with intermittent claudication (median age, 66 years; range, 56-80; ABPI, 0.69 [SD, 0.09]); group 3: 14 patients with rest pain (median age, 67.5 years; range, 54-84 years; ABPI, 0.45 [SD, 0.08]). In part 2, heparin equivalent to that in normal plasma was added to blood samples from 15 patients with short-distance claudication (n = 4) or rest pain (n = 11), and baseline (without heparinase) thromboelastography was performed to exclude lack of antithrombin as a cause of diminished heparin-like activity. RESULTS: In part 1, all patients with PAOD had a significant increase in coagulability compared with controls. Heparinase-modified thromboelastography in controls showed a significant decrease in the latent period between placing the sample in the analyser, where it is recalcified, to the initial fibrin formation (DeltaR time; P = .002) compared with native TEG, confirming endogenous heparin-like activity. Using DeltaR time as a measure of heparin-like activity, a significant reduction was found in patients with claudication (0.33 minutes; 95% confidence interval [CI], 0.004-0.65; P = .02) and in those with rest pain (0.25 minutes; 95% CI, -0.02 to 0.52; P = .02) compared with that in controls (0.78 minutes; 95% CI, 0.39-1.16). The DeltaR time also correlated with the ABPI (r = 0.35, P = .02), suggesting declining heparin-like activity with increasing ischemia. In part 2, exogenous heparin restored the thromboelastography in PAOD patients to normal, suggesting that lack of endogenous heparin-like compounds rather than reduced antithrombin levels was responsible for changes in coagulation. CONCLUSION: Patients with PAOD have reduced endogenous heparin-like activity that correlates with disease severity.